2002
DOI: 10.1063/1.1500789
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a capacitively coupled radio-frequency methane plasma: Comparison between a one-dimensional and a two-dimensional fluid model

Abstract: A comparison is made between a one-dimensional ͑1D͒ and a two-dimensional ͑2D͒ self-consistent fluid model for a methane rf plasma, used for the deposition of diamond-like carbon layers. Both fluid models consider the same species ͑i.e., 20 in total; neutrals, radicals, ions, and electrons͒ and the same electron-neutral, ion-neutral, and neutral-neutral reactions. The reaction rate coefficients of the different electron-neutral reactions depend strongly on the average electron energy, and are obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…15 In addition, the comprehensive two-dimensional fluid models have been successfully developed to numerically study CH 4 reforming. [26][27][28] Herrebout et al have compared a one-dimensional and a two-dimensional self-consistent fluid models for the CH 4 radio frequency plasma and have shown that the calculation results obtained with the two models are in relatively good agreement. 26 Babaeva et al have used the twodimensional simulator to research the interaction between plasma filaments in DBDs and liquid covered wounds.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…15 In addition, the comprehensive two-dimensional fluid models have been successfully developed to numerically study CH 4 reforming. [26][27][28] Herrebout et al have compared a one-dimensional and a two-dimensional self-consistent fluid models for the CH 4 radio frequency plasma and have shown that the calculation results obtained with the two models are in relatively good agreement. 26 Babaeva et al have used the twodimensional simulator to research the interaction between plasma filaments in DBDs and liquid covered wounds.…”
Section: Introductionmentioning
confidence: 93%
“…[26][27][28] Herrebout et al have compared a one-dimensional and a two-dimensional self-consistent fluid models for the CH 4 radio frequency plasma and have shown that the calculation results obtained with the two models are in relatively good agreement. 26 Babaeva et al have used the twodimensional simulator to research the interaction between plasma filaments in DBDs and liquid covered wounds. 27 Levko et al have studied non-thermal plasma ethanol reforming in argon bubbles immersed in liquids using a two-dimensional multi-species fluid model and have analyzed the main reactions responsible for the generation of molecular hydrogen and light hydrocarbon species.…”
Section: Introductionmentioning
confidence: 93%
“…The details are listed in Tables 3-6. Besides the inlet gas (CH 4 /H 2 ), some higher order neutral molecules (C 3 H 8 , C 2 H 6, C 2 H 4, C 2 H 2 ) are also included in our model, because they were found to be formed in the plasma at high densities [44]. Some radical and ionic species (e.g.…”
Section: The Plasma Chemistry For Cnt/cnf Growthmentioning
confidence: 99%
“…where i in Å 3 is the polarizability of the background gas and is taken from [44] and [47] for all ions. The overall ion mobility µ j of ion j in the gas mixture can again be obtained by Blanc's law; see above.…”
Section: Diffusion and Wall Deposition Lossesmentioning
confidence: 99%
See 1 more Smart Citation